2011
DOI: 10.4049/jimmunol.1001650
|View full text |Cite
|
Sign up to set email alerts
|

Negative Feedback Regulation of NF-κB Action by CITED2 in the Nucleus

Abstract: NF-κB is a family of important transcription factors that modulate immunity, development, inflammation, and cancer. The biological activity of NF-κB is subjected to various spatial and temporal regulations. Bioinformatics analysis predicts that CITED2 is topologically close to NF-κB in the protein interaction networks. In this study, we show that ectopic expression or knockdown of CITED2 attenuates or potentiates, respectively, the expression of NF-κB–responsive genes. Mechanistically, CITED2 constitutively lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 46 publications
3
66
0
Order By: Relevance
“…The exact mechanism through which GILZ impacts on DNA binding remains unclear. However, it is known that posttranslational modifications (e.g., phosphorylation and acetylation) of NF-kB are absolutely required for its optimal transcriptional activity (36)(37)(38), and, in many cases, these posttranslational modifications are able to alter transcriptional activity without affecting nuclear translocation (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism through which GILZ impacts on DNA binding remains unclear. However, it is known that posttranslational modifications (e.g., phosphorylation and acetylation) of NF-kB are absolutely required for its optimal transcriptional activity (36)(37)(38), and, in many cases, these posttranslational modifications are able to alter transcriptional activity without affecting nuclear translocation (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that Introduction 47 Hypoxia inducible factors (HIF) 1 1 and 2 are crucial to mediate 48 the cellular adaptation in response to hypoxia [1]. HIF-1 and HIF-2 49 are heterodimers formed by the oxygen-sensitive subunits, HIF-1a 50 and HIF-2a, and a constitutive subunit referred to as HIF-1b or 51 Arnt1. Under normoxic conditions, the oxygen, 2-oxoglutarate and 52 iron-dependent prolyl hydroxylases (PHDs) catalyse the hydroxyla- 53 tion of two key proline residues present in the oxygen-dependent 54 degradation domain (ODDD) of HIF-1a and HIF-2a, promoting their 55 recognition by the von Hippel-Lindau protein (pVHL) E3 ligase and 56 their subsequent degradation by the proteasome [2].…”
mentioning
confidence: 98%
“…665 Of particular interest, yeast two-hybrid screenings have pointed 666 out a potential interaction between FBXL5 and p300 in the human 667 liver protein network [47]. tion might also indirectly affect the acetylation process of tran-683 scription factors by CBP/p300, such as p53 and NF-jB [49,50]. 684 Since cellular iron and oxygen deprivation destabilizes FBXL5 and 685 promotes its own degradation by the proteasome [27,28], the 686 interaction between CITED2 and the CH1 domain of CBP/p300 687 might also be modulated by the cellular availability of iron and 688 oxygen.…”
mentioning
confidence: 99%
“…Bone marrow-derived macrophages (BMDMs) were obtained, as described previously (29). BMDMs were harvested after ∼6∼10 d and recultured in 12-well plates for small interfering RNA (siRNA) transfection using lipofectamine 2000 (Invitrogen) and further experiments.…”
Section: Cell Culture and Manipulation Of Primary Cellsmentioning
confidence: 99%